Development of The Ensiklopedia Tumbuhan Flipbook as a Science Learning Resource in Elementary School: Pengembangan Flipbook “Ensiklopedia Tumbuhan” Sebagai Sumber Belajar Sains di Sekolah Dasar - Setyaningrum, Fitriana Dwi; Masithoh, Dewi (SEARCH: Science Education Research Journal, 2025)
The development of science and technology has accelerated, so education needs new technology. Teachers are limited in their use of digital science learning media in elementary schools. Books are not being used as full science learning resources, so new learning media are needed. This study aims to develop a flipbook called "Ensiklopedia Tumbuhan" for elementary school students to learn science. This research constitutes a development study (Research and Development) employing the ADDIE model, which comprises the following stages: The sequence of these phases is as follows: analysis, design, development, implementation, and evaluation. The research was conducted from April 2022 to August 2023. The research subjects were fourth-grade students enrolled at SDIT Samawi, Bantul. The data collection techniques employed in this study involved the administration of questionnaires. The analysis employed quantitative descriptive analysis techniques, with data calculated using Microsoft Excel. The flipbook media "Ensiklopedia Tumbuhan" was deemed suitable based on evaluations by subject matter experts, media experts, and field testing results with elementary school students. Research results show that the "Ensiklopedia Tumbuhan" flipbook product is suitable for elementary science education, with an average score of 98.46% and the highest "A" rating from subject experts. The pilot test of the "Ensiklopedia Tumbuhan" flipbook as a learning resource also had an average score of 86% in the "highly suitable" category.